72.8k views
3 votes
H(x)= -x^3-2x^2-3x+4; x=2

User Kennethvr
by
5.5k points

1 Answer

5 votes

Answer:

h(2) = -18

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Algebra I

  • Function Notation

Explanation:

Step 1: Define

h(x) = -x³ - 2x² - 3x + 4

x = 2

Step 2: Evaluate

  1. Substitute: h(2) = -(2)³ - 2(2)² - 3(2) + 4
  2. Exponents: h(2) = -8 - 2(4) - 3(2) + 4
  3. Multiply: h(2) = -8 - 8 - 6 + 4
  4. Subtract: h(2) = -16 - 6 + 4
  5. Subtract: h(2) = -22 + 4
  6. Add: h(2) = -18
User James Davis
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.